2015
DOI: 10.3329/jcamr.v2i1.22581
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity among Caregivers of Schizophrenia Patients – A Study in Tertiary Care Psychiatric Hospital in Dhaka

Abstract: Background: Severe mental illness like schizophrenia has far-reaching consequence for both patients and caregivers and their relatives and they also experience feeling of loss and grief. They are confronted with uncertainty and emotion of shame, guilt and anger like the patients they feel stigmatized and socially isolated. Caring for a family member with schizophrenia is an enduring stressor and causes considerable amount of burden. Objective: To assess mental health status of the caregivers of schizophrenia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…The significant relationship between patient's level of functioning and psychiatric morbidity among caregivers of those with schizophrenia is similar to findings from previous studies (8,21). Less severe functional impairment in patients and more periods of relatively normal functioning in patients with bipolar affective disorder when compared to schizophrenia may explain higher psychiatric morbidity among caregivers of the latter illness.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The significant relationship between patient's level of functioning and psychiatric morbidity among caregivers of those with schizophrenia is similar to findings from previous studies (8,21). Less severe functional impairment in patients and more periods of relatively normal functioning in patients with bipolar affective disorder when compared to schizophrenia may explain higher psychiatric morbidity among caregivers of the latter illness.…”
Section: Discussionsupporting
confidence: 79%
“…This study revealed a high prevalence of psychological morbidity in caregivers of patients with schizophrenia and bipolar affective disorder, which is comparable to those reported in previous studies (21,22). Both these illnesses are chronic in nature and the patients usually require ongoing assistance, which may lead to caregiver frustration and burn out.…”
Section: Discussionsupporting
confidence: 74%
“…Within two-weeks of this initial assessment, a psychiatrist working as part of our research team undertook a clinical assessment with these patients using the depression module of the Bengali version of the Structured Clinical Interview for DSM-IV (SCID) [22]. The SCID is a well-used tool for psychiatric assessments and has been used in previous studies in Bangladesh [23,24]. In our study, the depression module of the research version of this tool was used.…”
Section: Cross-sectional Survey Measuresmentioning
confidence: 99%
“…4,6,9 Such differences may be due to different selection criteria, inclusion of different psychiatric disorders, different tools of evaluation and cultural variations. 10 76.7% female caretakers were suffering from depression compared to 67.7% male caretakers. Low self esteem may result from the emotional attachment of the female caretakers with their patients.…”
Section: Discussionmentioning
confidence: 92%